Rapid, application-based survey to characterise the impacts of COVID-19 on LGBTQ+ communities around the world: an observational study. Issue 4 (12th April 2022) - Adamson, Tyler; Hanley, Marguerite; Baral, Stefan; Beyrer, Chris; Wallach, Sara; Howell, Sean
Abstract : Introduction: Emerging evidence indicates that the COVID-19 pandemic, and the responses it has generated, have had disproportionate impacts on lesbian, gay, bisexual, transgender and queer (LGBTQ+) communities. This study seeks to build on existing information and provide regional insight. Methods: In response, a cross-sectional survey was administered to a global sample of LGBTQ+ individuals (n=13 358) between 16 April and 20 May 2020 via the social networking application Hornet. The survey contained questions that characterise the impact of COVID-19 and associated mitigation strategies on economics, employment, mental health and access to healthcare. Results: 5191 (43.9%) individuals indicated they were somewhat, slightly or unable to meet basic needs with their current income, while 2827 (24.1%) and 4710 (40.1%) felt physically or emotionally unsafe in their living environment, respectively. 2202 individuals (24.7%) stated they are at risk for losing health insurance coverage. 2685 (22.7%) persons reported having skipped or cut meals as there was not enough money. Conclusion: Many LGBTQ+persons who responded reported adverse consequences to mental health, economics, interruptions to care and lack of support from their government. This data is part of ongoing analyses but accentuates the unique needs of LGBTQ+ communities that will require targeted, ameliorative approaches.